Intrinsically Photoswitchable α/β Peptides toward Two‐State Foldamers. (15th July 2018) - Marafon, Giulia; Crisma, Marco; Moretto, Alessandro
Abstract: A simple, unsaturated, E – Z photoisomerizable β‐amino acid, ( Z )‐3‐aminoprop‐2‐enoic acid, has been introduced into peptide foldamers through a one‐pot chemical coupling, based on Pd/Cu‐catalyzed olefin oxidative amidation, between two peptide segments carrying, respectively, a ‐Gly‐NH2 residue at the C‐terminus and an acryloyl group at the N‐terminus. Reversible conversion between the Z and E configurations of the 3‐aminoprop‐2‐enoic linkage was achieved photochemically. A crystallographic analysis on two model compounds shed light on the consequences, in terms of 3D structure and self‐association properties, brought about by the different configuration of the unsaturated linkage. As a proof of concept, E – Z photoisomerization of a 3‐aminoprop‐2‐enoic acid residue, inserted as the junction between two conformationally distinct peptide domains (one helical while the other β‐sheet promoter), allowed supramolecular self‐association to be reversibly turned on/off.